Kyrgyz Republic Economic Update No. 8, Fall/Winter 2018 : Weak Growth Despite Emerging Regional Opportunities - World Bank Group (World Bank, Washington, DC, 2019)
Real GDP growth slowed to 3.1 percent in January-November 2018 from 3.7 percent in the same period of 2017. This deceleration was the result of slower growth in both gold production and non-gold industry. Export performance remains weak, largely on account of a sharp slowdown in gold exports, and in spite of trade opportunities within the Eurasian Economic Union. Attracting private investment remains a challenge. Recent developments point to limited progress in addressing structural issues over the past few years. While the Kyrgyz Republic was able to avoid an external shock driven recession in 2014-15, the economy remains vulnerable to external economic shocks given its high dependence on an undiversified export base, workers’ remittances, and foreign aid.The fiscal position has improved with a strong tax revenue performance and cuts to capital outlays. This has helped keeping public debt under control following a sharp increase in 2014-15. With inflation pressures low, the monetary policy stance remains relaxed. The National Bank reduced its policy rate by 25 basis points to 4.75 percent in May 2018 to support economic growth and has maintained a managed float of the exchange rate.Going forward, real GDP growth is forecast to accelerate slowly to 3.9 percent by 2020 supported by all the major sectors – industry, agriculture, construction and services. On the demand side, growth is projected to be driven by private consumption, investment and exports. The economy will continue to benefit from large remittance inflows and firming external demand. Strong remittances will support average consumption growth of around 3 percent in 2018–20. However, the current account deficit is projected to remain elevated at about 9 percent of GDP, reflecting structural constraints, the significant import content of public investment, and an indirect feed-through effect of remittances via imports. To rebuild fiscal buffers, the authorities are committed to reducing the deficit to 3 percent of GDP by 2020.